Quasi-static test data set of honeycomb hybrid tubes by FDM 3D printingMendeley Data - Fina Andika Frida Astuti; Moch. Agus Choiron; Anindito Purnowidodo; Yudy Surya Irawan (Data in Brief)
Crash box development is carried out continuously to obtain a lightweight design and high energy absorption. This dataset presents the results of a crash box experiments. Quasi-static testing of aluminum, honeycomb, and hybrid tube specimens was carried out using a universal testing machine. The load given in the quasi-static test was a constant load. Force and displacement data were collected by the system while the failure process was captured by a digital camera. The data set presented includes the final deformation patterns of aluminum and honeycomb. This dataset also displays the crushing process of honeycomb and hybrid tube. Force and displacement data from each specimen are also presented to determine energy absorption. Crashworthiness indicators are calculated to complete the crashworthiness of the crash box. The results of this experiment can be used for the development of a crash box as a vehicle safety device.